Nanocomposite and Nanostructured Carbon-based Films as Growth Substrates for Bone Cells - Bacakova, Lucie; Grausova, Lubica; Vacik, Jiri; Kromka, Alexander; Biederman, Hynek; Choukourov, Andrei; Stary, Vladimir (IntechOpen, 2011)
None